A Theoretical Investigation on CO Oxidation by Single‐Atom Catalysts M1/γ‐Al2O3 (M=Pd, Fe, Co, and Ni). Issue 7 (16th March 2017) - Yang, Tao; Fukuda, Ryoichi; Hosokawa, Saburo; Tanaka, Tsunehiro; Sakaki, Shigeyoshi; Ehara, Masahiro
Abstract: Single‐atom catalysts have attracted much interest recently because of their excellent stability, high catalytic activity, and remarkable atom efficiency. Inspired by the recent experimental discovery of a highly efficient single‐atom catalyst Pd1 /γ‐Al2 O3, we conducted a comprehensive DFT study on geometries, stabilities and CO oxidation catalytic activities of M1 /γ‐Al2 O3 (M=Pd, Fe, Co, and Ni) by using slab‐model. One of the most important results here is that Ni1 /Al2 O3 catalyst exhibits higher activity in CO oxidation than Pd1 /Al2 O3 . The CO oxidation occurs through the Mars van Krevelen mechanism, the rate‐determining step of which is the generation of CO2 from CO through abstraction of surface oxygen. The projected density of states (PDOS) of 2 p orbitals of the surface O, the structure of CO‐adsorbed surface, charge polarization of CO and charge transfer from CO to surface are important factors for these catalysts. Although the binding energies of Fe and Co with Al2 O3 are very large, those of Pd and Ni are small, indicating that the neighboring O atom is not strongly bound to Pd and Ni, which leads to an enhancement of the reactivity of the O atom toward CO. The metal oxidation state is suggested to be one of the crucial factors for the observed catalytic activity. Abstract : Low cost, high efficiency : Density functional theory calculations revealed that single‐atom catalyst Ni1 /γ‐Al2 O3 has higher thermal stability and catalytic activity towards CO oxidation than Pd1 /γ‐Al2 O3 .